"You want protected bike lanes, I want protected Black children. Let's link": equity, justice, and the barriers to active transportation in North America. Issue 12 (2nd December 2021) - Agyeman, Julian; Doran, A.
ABSTRACT: Since the early 2000s, academic research on equity and justice has become an increasingly integral component of transportation planning and policy-making. Less research, however, has focused specifically on the intersection of equity, justice, and active transportation (i.e. cycling and walking). This Viewpoint builds on some of the key concerns and barriers associated with active transportation for disadvantaged groups, especially but not exclusively in relation to planning culture and processes, policing, harassment and racism, and gentrification and displacement. We investigate how issues of equity and justice can worsen the conditions that often prevent or diminish one's capability or desire to engage in active transportation. By providing a better understanding of the deep intersectionalities of equity, justice, and the physical and social barriers to active transportation, our hope is that this Viewpoint helps to improve how such barriers can be recognised and overcome, and the opportunities for change can be understood, centred, and implemented at the policy and planning level.